Al-Qur'an Transformation In The Digital Era : Analysis Of Literature Concerning Online Tafsir And The Application - Sridefi, Syafna; Hafiz, M; Permana, Robi Agus; saputra, Alam; Motivaria, Mega Adyna (International Journal of Research, 2024)
This article discusses the Transformation of interpretation of the Qur'an, in the era of digital in the analysis of literature through online interpretation its applications are youtube , instagram , facebook , twitter as well as through other websites that benefit to learning interpretations of the Qur'an ' an, the purpose of this research to know the transformation of translation of the Qu r ' an in the age in digital , that the learning model in the digital era is undergoing significant changes compared to the traditional model, which uses technology to improve access and interaction in learning, such as online teaching, learning that takes place online and on-line, and access to interpret the Qur'an through social media and dedicated websites. The type of research used is library research or library study that uses an analytical descriptive approach that uses books, articles, journals, and related references to find problems and answer important questions about the interpretation of the Qur'an online .